A prospective comparative study to assess the management outcomes of patients with infantile hypertrophic pyloric stenosis using ramstedt's pyloromyotomy and double 'Y' pyloromyotomy - Arun Kumar Dash; Rakesh Sahoo; P K Mohanty; P K Jena; A K Panda; P K Tripathy (Wolters Kluwer Medknow Publications, 2023)
Background: Infantile hypertrophic pyloric stenosis (IHPS) is the most common cause of gastric outlet obstruction in infancy in which the pyloric portion of the stomach becomes hypertrophied, leading to obstruction of gastric emptying. Various approaches have been tried for surgical management of IHPS. The first successful surgery was performed by Dufour and Fredet in which the hypertrophic pyloric muscle is longitudinally splitted and closed transversely. However, Ramstedt introduced extramucosal pyloromyotomy, introduced in 1912 which still remains the gold standard for surgical management of IHPS. Later on, in 2009, Alayet et al. introduced a new technique known as Alayet's double-Y (DY) pyloromyotomy which he claimed to have a better functional outcome compared to Ramstedt's pyloromyotomy (RP) while maintaining a safety profile similar. The objective of this study was to compare the outcome of surgical management of IHPS between DY pyloromyotomy and Ramstedt's pyloromyotomy. Materials and Methods: It was a prospective study conducted in the Paediatric Surgery Department of SVPPGIP, SCB Medical College, Cuttack, from January 2019 to April 2022. All the IHPS cases were admitted and optimised thoroughly with regard to hydration, acid-base status and electrolyte imbalance. We have included 60 patients and were divided into two groups; every alternate patient was pooled into one group. Detailed and informed consent was taken from parents regarding the surgical procedure of their baby. The patients were selected alternatively, i.e., if one patient underwent Ramstedt's pyloromyotomy then in the next patient Alayet's DY pyloromyotomy procedure was done. The demographic characteristics of all patients, operative procedure performed, duration of surgery, intraoperative anaesthesia or surgical complication, post-operative vomiting patterns and weight gain data were collected and analysed in Microsoft Excel sheet and SPSS software. The student's t-test was used to compare both groups. Results: We found that both groups were similar while considering the demographic characteristics as there were no significant statistical differences noticed in the patient population with regard to age (DY Group 42.73 ± 9.01 days vs. RP Group 40.63 ± 7.6 days; P = 0.8209), sex (DY 4F/26M vs. RP 6F/24 M), weight at presentation (DY 3.3 ± 0.33 kg vs. RP 3.2 ± 0.21 kg; P = 0.33449), symptoms and clinical condition. All patients were optimally resuscitated before proceeding to surgery with regard to hydration, electrolyte imbalance and acid-base status. While considering anaesthesia, both groups were equal in terms of it and no anaesthesia-related complications were recorded in our study. However, during the first post-operative week, a significant difference was noted between DY versus RP groups with regard to vomiting (DY 1.33 ± 0.59 days vs. RP 2.8 ± 0.76 days; P = < 0.0001) and weight gain (299.86 ± 41.90 g vs. 199.03 ± 21.72 g; P = 0.008), respectively. Patients were followed up for 6 months post-operatively. No long-term complications were noticed in both groups. Weight gain after 1 month DY 577.46 ± 169.96 g versus RP 574.70 ± 170.10 g, (P = 0.949969), after 2 months DY (758.43 ± 94.53 g vs. RP 758. 8 ± 94.68 g, P = 0.98699) and after 3 months DY (593 ± 20.01 g vs. RP 591.16 ± 20.89 g, P = 0.61136). Overall, the operative time duration was the same in both groups. We had not noticed any intraoperative complications, post-surgical site infections were encountered. There was no need to redo pyloromyotomies in our study. Conclusion: Our study demonstrated that the double-Y pyloromyotomy procedure provides a better functional outcome with regard to vomiting and weight gain in the early post-operative period. It seems to be due to the wider opening of the pyloric canal at both ends of pyloromyotomy incision with a wide angle compared to Ramstedt's pyloromyotomy. Obviously, the chance of mucosal perforation is also less as the enforce of the mucosa is divided into two directions. The method is suitable for both conventional and laparoscopic surgery. The small sample size was a limiting factor in this study. However, more studies need to be done on this technique to prove its efficacy and establish it as a standard technique for the future.